Chegamos à pós-graduação, e agora? implementação de políticas de ações afirmativas para pessoas com deficiência no stricto sensu das universidades federais brasileiras - Joyce fernandes de Freitas (2024)
The analysis and application of affirmative action policies aimed at people with disabilities in higher education have been a topic of investigation both in Brazil and internationally. However, it is imperative to expand understanding in this field, especially in postgraduate studies. Therefore, the general objective of this study was to analyze the impact of Normative Ordinance No. 13, of May 11, 2016 (under political aspects, entry into postgraduate studies and implementation of the normative). And its specific objectives were to identify changes in the internal policies of the agency that regulates the operation of stricto sensu postgraduate studies in Brazil, with the purpose of complying with Normative Ordinance No. 13, of May 11, 2016; analyze the compliance of this ordinance and its effect on the entry of people with disabilities into stricto sensu postgraduate studies at Brazilian Federal Universities; verify how the implementation of the ordinance occurred at the Federal University of Minas Gerais, in order to encourage the entry and retention of People with Disabilities in stricto sensu Postgraduate Studies. This research is descriptive and in terms of procedures, it is characterized as bibliographic and documentary. The data sources were APCN documents and Mid-Term seminars from Capes' 50 assessment areas, affirmative action resolutions from Brazilian federal universities, number of students with disabilities in postgraduate studies and scholarship students, obtained through LAI in the FALABR system, UFMG affirmative action resolutions, scholarship resolutions for postgraduate programs, supplementary notices from UFMG, number of students with disabilities in the Stricto sensu postgraduate course at UFMG, Minutes, meeting documents, UFMG PDI. After analyzing this data, it was possible to conclude that the Normative Ordinance 13/2016 was complied with by 38 of the 69 Brazilian federal universities, and that the number of students registered on the Capes Sucupira Platform as people with disabilities grew 264% since 2017, the year in which the record started to be inserted into the platform. Since 2023, Capes has started to encourage discussion about affirmative actions, in the areas of evaluation, and in mid-term seminars. UFMG's Normative Ordinance 02/2017 contributed to an increase in the number of students with disabilities at the institution. Nomenclature errors were found in several area documents, and in the UFMG resolution. Despite the increase in the number of students with disabilities in postgraduate studies, there is much to be done and discussed to provide access and, mainly, the permanence of people with disabilities in stricto sensu postgraduate studies in Brazil